Reducing Physical Health Inequalities: A Community Mental Health Clinic Quality Improvement Project - Murtala Abdussalam; Tanisha Smith (BJPsych Open, 2025)
Aims: People with severe mental illness (SMI) experience greater physical health inequalities, poorer health outcomes and significantly lower life expectancy (15–20 years) than the general population. Despite National and local guidelines on routine physical monitoring to mitigate these inequalities, the practice in this clinic is inconsistent, often fraught with delays and inefficiencies. This quality improvement project (QIP) aims to achieve full compliance with monitoring guidelines to 100% over 8 weeks, enhancing patient safety and outcomes.